Aligning School with Society: A Rogoffian Analysis of Behavioural Challenges in Bangladeshi Schools - Haque, Md Tozammel (Journal of Education Culture and Society, 2026)
Aim. The purpose of the study is to address the applicability of guided participation in Non-Western contexts along with the Bangladeshi perspectives. The study also tries to explore the behavioural challenges of the learners that arise from non-contextual teaching-learning activities in Bangladesh. Method. Guided Participation was the core theoretical framework to address the issues for this study. Interpretative analysis was applied to collect information for the study from various sources such as historical documents, library sources like books, journals, scholarly articles, documentations, government websites, newspapers, and other secondary sources. Results. The data reflects the findings that human learning development is a dynamic and collaborative process where individuals learn within the tapestry of their social and cultural worlds using social tools. In terms of Bangladesh, here the education system is rigid, teacher-centred, full of rote memorisation which emphasises individual performance, competition with peers, tests and exam results. This gap between the guided learning at home and the formal schooling system creates confusion and frustration among students and leads to behavioural challenges such as disengagement, lack of motivation, or disruptive behaviour and inattention to learning. Conclusions. These findings may offer some guidance and information for future educators and authorities so that they can formulate an education policy that is convenient for learners.